Discourse Patterns and Communicative Approaches for Teaching Nature of Science - (:unkn) unknown (TURKISH EDUCATION ASSOC, 2016)
This study aims to determine discourse patterns and communicative approaches utilised for teaching the nature of science (NOS) using an explicit-reflective approach. This study was conducted as part of a research project aiming to support teachers' classroom practices through a long-term professional development program focusing on teaching NOS. Discourse analysis was used to determine classroom discourse patterns and communicative approaches. Audio and video recordings of classroom lectures conducted by 8 of the 22 teachers participating in the project were used for analysis. A total of 505 minutes of teacher-student dialogue was recorded and subsequently analysed. The results indicated that teachers used three different discourse patterns (triadic, chain, and adjacency pair) and three different communicative approaches (interactive-dialogic, interactive-authoritative, and non-interactive-dialogic) for teaching NOS using the explicit-reflective approach. The most common discourse pattern was the triadic pattern (initiation-response-evaluation), and the interactive-authoritative approach was the most common communicative approach. These findings contribute to the literature in terms of increasing the efficiency of using the explicit-reflective approach by considering classroom discourse to teach students NOS.
Keywords: Nature of science; Science education; Discourse analysis; Discourse patterns; Communicative approaches; TEACHERS CONCEPTIONS; EXPLICIT; VIEWS; STUDENTS; INQUIRY